ANALISIS PERHITUNGAN DESAIN LAYOUT GUDANG SPAREPART KAPAL PADA KANTOR CABANG MERAK - BAKAUHEUNI PT. ASDP - Mulyati, Erna; Hamidin, Dini; maniah, Maniah; Hidayat, Syamsu (LAND JOURNAL, 2024)
PT ASDP is a company engaged in the field of water transportation. Its main function is to provide access to inter-island public transportation as well as transportation access to areas that do not yet have crossings. Maintenance of ships at PT. ASDP is a must, so the speed of warehouse services in providing spare parts is important. Currently, the spare parts storage warehouse belongs to a third party (BGR warehouse) which shows a large accumulation of goods. This will result in damage if the spare part has a limited-service life and an increase in warehouse rental costs on third parties. Therefore, PT ASDP plans to transfer its spare parts to branch warehouses in Merak and Bakauheuni. This study aims to determine the layout design of the ship spare parts warehouse for PT ASDP branch offices in Merak and Bakauheuni using the class-based storage method, along with the calculation of the needs of using racks and bins. The result of the study is the layout design of the Bakauheni and Merak branch warehouses along with racking and bin needs that can be used as a reference for PT. ASDP in simplifying the process of inbound and outbound spare parts.